Implementasi Fuzzy Logic Control pada Pelacakan Panel Surya - Angga Juliat Saputra; Bayu Erfianto; Mas'ud Adhi Saputra; SIDIK Prabowo; Novian Anggis Suwastika (Balai Besar Bahan dan Barang Teknik, 2019)
A dynamic solar panel equipped with a fuzzy-method tracking system has been developed to improve its performance. In this solar panel with tracking system, the voltage and current of the solar panels were used as inputs for the fuzzy algorithms. From observations for seven days, dynamic and static solar panels produced the highest voltage of 21.65 V and 20.13 V, as well the highest current of 0.58 A and 0.54 A respectively. Dynamic solar panel could produce an average voltage of 19% and an average current of 16% higher than static solar panels. The length time of battery charging on a dynamic solar panel was one hour shorter than that of static solar panel.Panel surya dinamis yang dilengkapi sistem pelacakan dengan metoda fuzzy telah dikembangkan untuk meningkatkan kinerjanya. Dalam panel surya dengan sistem pelacakan ini, tegangan dan arus dari panel surya digunakan sebagai input untuk fuzzy algorithms. Dari pengamatan selama tujuh hari, panel surya dinamis dan statis menghasilkan berturut-turut tegangan tertinggi 21,65 V dan 20,13 V, serta arus 0,58 A dan 0,54 A. Panel surya dinamis dapat menghasilkan tegangan rata-rata 19% dan arus rata-rata 16% lebih tinggi daripada panel surya statis. Lama waktu pengisian baterai pada panel surya dinamis satu jam lebih singkat daripada panel surya statis.